Meat quality of Italian Simmental young bulls as affected by the genes frequency of Montbéliarde origin - S. Failla; P. Pittia; A. Sepulcri; L.A. Volpelli; R. Valusso; E. Piasentier (Italian Journal of Animal Science, 2011)
Italian Simmental (IS) is the most common dual-purpose breed in Italy. In the '90s, when high amounts of capital were invested for the transformation from tie-standing to loose housing stable, the farmers strongly stated their will for the improvement of milk production, udder conformation and of milk flow rate. The National Breeders' Association conceded a controlled introduction of the best Montbéliarde (Mb) bulls, the French strain of Simmental breed (Besozzi, 1996), which has been continuously improved for milk production. At present, the frequency of genes of Mb origin in the IS population is important, as proved by the Italian breeders' index: among the Rank90 bulls, 17 animals (out of 69) have >25% Mb genes (ANAPRI, 2002).....